2022
DOI: 10.3390/ijerph191911960
|View full text |Cite
|
Sign up to set email alerts
|

A Realist Review of How Community-Based Drug Checking Services Could Be Designed and Implemented to Promote Engagement of People Who Use Drugs

Abstract: With rising numbers of drug-related deaths in the UK and globally, exploration of interventions that seek to reduce drug-related harm is essential. Drug checking services (DCS) allow people to submit drug samples for chemical analysis and receive feedback about the sample, as well as harm reduction advice. The use of DCS is often linked to festival and/or nightlife settings and to so-called ‘recreational’ drug use, but research has also shown the potential of community-based DCS as an intervention serving more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…As a harm reduction intervention, we argue that drug checking holds potential for impact beyond an individual level, on the unregulated drug market as well as at the community and policy level [ 2 , 121 ]. However, public health and harm reduction organizations lack clear guidance to inform decisions on which instruments to purchase [ 122 ]. They currently do not have sufficient opportunities to assess what the operation of such instruments would actually look like in practice, with numerous potential benefits and limitations to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a harm reduction intervention, we argue that drug checking holds potential for impact beyond an individual level, on the unregulated drug market as well as at the community and policy level [ 2 , 121 ]. However, public health and harm reduction organizations lack clear guidance to inform decisions on which instruments to purchase [ 122 ]. They currently do not have sufficient opportunities to assess what the operation of such instruments would actually look like in practice, with numerous potential benefits and limitations to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of what instrument is employed, the recognition and understanding of the sources of uncertainty and limitations is at the forefront of providing a safe and reliable service model. Pragmatic knowledge translation is vital to establishing a trustworthy service [ 122 ]. For many service providers the reality is that current out-of-the-box technology is not meeting their needs [ 29 ], particularly in the level of nuance and expertise required for the interpretation of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Test results alone are a source of information which can be used for a multitude of purposes aside from harm reduction and dissemination of test results does not necessarily in itself result in the reduction of drug-related harm. Regardless of the model chosen, organisations wishing to get started can use operational guidelines (Masterton et al , 2022; Trans European Drug Information, 2022). In addition to being evidence-based, we suggest here that drug checking should be evidence-making (Trans European Drug Information, 2022; Wallace et al , 2022).…”
Section: Recommendationsmentioning
confidence: 99%
“…Trials in this field have reported numerous models (e.g., employing spectroscopic and chromatographic techniques as well as presumptive tests) and improved developments in the detection and identification of illicit and novel drugs, although they are often associated with mixed opportunities and challenges [ 3 , 29 , 30 ]. Portable in-field techniques with their screening ability are usually easy to use and beneficial in providing a low-cost rapid identification of the content of the sample and informing on decisions accordingly (e.g., advice on harm, providing intelligence information, preparing for possible threats from high-risk drugs) [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%